MENINGKATKAN KEMAMPUAN FISIK MOTORIK KASAR ANAK MELALUI PERMAINAN TRADISIONAL PLETOKAN PADA KELOMPOK B TKM NU 169 KHUBBUL WATHON CERME GRESIK - Nina Nuriyah Ma'arif; Mulyati (Atthiflah: Journal of Early Childhood Islamic Education, 2021)
Physical motor is one of the areas of development in early childhood education. Pletokan game is one of the games associated with the process of physical motor development. This study discusses the effectiveness of traditional pletokan games in improving the gross motor skills of children in group B at TKM NU 169 Khubbul Wathon Cerme Gresik. Using the classroom action research (CAR) method, the results have revealed that the role of pletokan game in developing gross motor skills of children in Group B TKM NU 169 Khubbul Wathon Cerme Gresik is regarded succesful. It can be seen from the observation sheet for gross motor skills that traditional game of pletokan in the first cycle (61%) and in the second cycle (86%). Additionally, the children's playing ability is very good, that is 0% in the first cycle, then increase to 57.1% in the second cycle.